Probucol inhibits oxidative modification of low density lipoprotein. - Parthasarathy, S (1986)
Previous studies have established that low density lipoprotein (LDL) incubated with endothelial cells (EC) undergoes extensive oxidative modification in structure and that the modified LDL is specifically recognized by the acetyl LDL receptor of the macrophage. Thus, in principle, EC-modified LDL could contribute to foam cell formation during atherogenesis. Oxidatively modified LDL is also potentially toxic to EC. The present studies show that addition of probucol during the incubation of LDL with EC prevents the increase in the electrophoretic mobility, the increase in peroxides, and the increase in subsequent susceptibility to macrophage degradation. It has also been shown that oxidation of LDL catalyzed by cupric ion induces many of the same changes occurring during EC modification. Addition of probucol (5 microM) also prevented this copper-catalyzed modification of LDL. Most importantly, samples of LDL isolated from plasma of hypercholesterolemic patients under treatment with conventional dosages of probucol were shown to be highly resistant to oxidative modification either by incubation with endothelial cells or by cupric ion in the absence of cells. The findings suggest the hypothetical but intriguing possibility that probucol, in addition to its recognized effects on plasma LDL levels, may inhibit atherogenesis by limiting oxidative LDL modification and thus foam cell formation and/or EC injury. Other compounds with antioxidant properties might behave similarly.